2018
DOI: 10.3892/ol.2018.7952
|View full text |Cite
|
Sign up to set email alerts
|

Monopolar spindle-one-binder protein 2 regulates the activity of large tumor suppressor/yes-associated protein to inhibit the motility of SMMC-7721 hepatocellular carcinoma cells

Abstract: Abstract. Accumulating evidence implicates monopolar spindle-one-binder protein (MOB)2 as an inhibitor of nuclear-Dbf2-related kinase (NDR) by competing with MOB1 for interaction with NDR1/2. NDR/large tumor suppressor (LATS) kinases may function similarly to yes-associated protein (YAP) kinases and be considered as members of the Hippo core cassette. MOB2 appears to serve roles in cell survival, cell cycle progression, responses to DNA damage and cell motility. However, the underlying mechanisms involved rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Additional functions for NDR kinases and Mobs are just beginning to show up from unbiased screens in distinct cell types, whether based on traditional genetics, RNAi, chemical genetics or protein-protein interactions. The potential for crossregulation and/or competition between Warts/LATS kinases and Tricornered-like kinases is apparent through their regulation by shared Class I Mob and Hippo activators but is only beginning to be investigated in detail (Zhang et al, 2018). Our understanding of both Mobs and Hippo pathway signaling would benefit from experiments to directly test whether a Mob-NDR kinase partnership and STRIPAK antagonism influence the pathway output in each new cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…Additional functions for NDR kinases and Mobs are just beginning to show up from unbiased screens in distinct cell types, whether based on traditional genetics, RNAi, chemical genetics or protein-protein interactions. The potential for crossregulation and/or competition between Warts/LATS kinases and Tricornered-like kinases is apparent through their regulation by shared Class I Mob and Hippo activators but is only beginning to be investigated in detail (Zhang et al, 2018). Our understanding of both Mobs and Hippo pathway signaling would benefit from experiments to directly test whether a Mob-NDR kinase partnership and STRIPAK antagonism influence the pathway output in each new cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, it was documented that hMOB2 could compete with hMOB1 for NDR1/2 binding, with hMOB2 counteracting hMOB1 as a co-activator of NDR1/2 [1,35,61]. In this context, Zhang et al studied Hippo signalling in a hMOB2 knockout hepatocellular carcinoma (HCC) cell line [62]. They found that MST1/2-mediated phosphorylation of NDR1/2 was induced, while MST1/2-mediated phosphorylations of hMOB1 and LATS1/2 were decreased upon hMOB2 knockout [62].…”
Section: An Overview Of Mobs and The Hippo Pathwaymentioning
confidence: 99%
“…In this context, Zhang et al studied Hippo signalling in a hMOB2 knockout hepatocellular carcinoma (HCC) cell line [62]. They found that MST1/2-mediated phosphorylation of NDR1/2 was induced, while MST1/2-mediated phosphorylations of hMOB1 and LATS1/2 were decreased upon hMOB2 knockout [62]. LATS1/2-mediated phosphorylation of YAP was also reduced in hMOB2 knockout cells, while MOB2 overexpression resulted in opposite effects [62].…”
Section: An Overview Of Mobs and The Hippo Pathwaymentioning
confidence: 99%
See 2 more Smart Citations